Application of the acoustoelastic effect in measurements of residual stresses - DEPUTAT, J. (Archives of Acoustics, 1990)
This paper contains a review of non-destructive methods of residual stress measurements and results of research on the properties of the acoustoelastic effect with regard to its application in investigations of stress fields in technological materials. Values of acoustoelastic constants and temperature coefficients of velocity change were determined in several construction metals for various types of waves. Relations between wave velocity and texture, influence of texture in ultrasonic measurements of stress are presented. Ultrasonic measurement methods of absolute values of stress in screws, railway rails and railway wheels were proposed. Constructed ultrasonic meter of residual stress are described and results of comparative X-ray, ultrasonic and destructive tests are given.